RAMPAK BARONG PADA PERTUNJUKAN JARANAN PAGUYUBAN TURONGGO SETYO JATI DI KABUPATEN BLITAR - Juwita Dwi Setyawati; Sumargono Sumargono (Institut Seni Indonesia Surakarta, 2021)
Rampak Barong dance, which is in a jaranan performance of Paguyuban Turonggo Setyo Jati in Blitar is a dance that belongs to a folk dance, which is a dance that lives and develops in the local communities with the simplicity of movement, floor patterns, make-up and even costume, because all of that are the characteristics of folk dance. This study aims to reveal the form of the performance and the function of that dance. Rampak Barong dance is very popular among the local community because there are many attractive movements including forward somersaults, interesting foot movements including srimpetan and junjungan. It become more interesting not only because of all kind of movements, but also there is one of main movement called nyaplok. The theoretical basis used to answer the problem of form is Soedarsono's theory in his book entitled “Introduction to Dance Elements and Dance Problems”, and supported by Soedarsono's opinion in his book entitled “Indonesian Performing Arts in Globalization” to describe the functions. The methodology used for this research are nterview, observation, and literature study. This research used descriptive analysis method used to describe the Rampak Barong dance. The results of this researh showed that the form of the dance performance Rampak Barong Paguyuban Turonggo Setyo Jati consists of several dance offerings with several elements of the dance offerings, such as dancers, movement, make-up, music, and performance venues. The function of the Rampak Barong dance as a means of ritual, as personal entertainment and as an aesthetic presentation, namely through ticketing performances or fundraisingKeywords: Form, Function, Rampak Barong, Turonggo Setyo Jati